X+y= 1, -2x+4y=6 solve use substitute


X+y=1 Subtract y from both sides x=-y+1 Substitute into the other equation -2(-y+1)+4y=6 Divide by -2 -y+1+2y=3 Subtract 1 -y+2y=2 Add like terms Y=2 Substitute into first equation X+2=1 Subtract 2 from both sides X=-1 (-1,2) I hope this helps :) -2(-y+1)+4y=6 2y-2+4y=6 2y+4y=12 6y=12 Y=2 ^^Another way to do the substitution

0 0
Only authorized users can leave an answer!
Can't find the answer?

If you are not satisfied with the answer or you can’t find one, then try to use the search above or find similar answers below.

Find similar answers

More questions